O encontro entre ensino de História e Patrimônio Cultural: uma proposta a partir da educação de jovens e adultos (Santo André-SP) - Ferrini, Juliana Esperanca [UNIFESP] (2019)
This work aims to discuss the historicity and production of memory related to the territory that today composes the municipality of Santo Andre. This subject has been studied with the students of the Education for Young People and Adults program (EJA), who are composed mostly by people of migrant origin. Through the conventional memories produced about the municipality and the power relations crystallized in the municipal, state and federal processes of patrimonialization, we can also reflect on the vestiges of the past and how it dialogues with us in the present, within the History teaching. For this, we chose the Paranapiacaba village as object of study and discussion. Recognized as a historic site by Brazilian government, and candidate for a UNESCO World Heritage Site, the village provides elements that address the issues raised during the research: the passage of time, the formation of territory, migrations, work, patrimony and its preservation. At the end, we suggest a sequence of activities created from the teaching practice with students of EJA in a municipal primary school (EMEIEF Cândido Portinari). Such sequence may also be appropriate and used by other interested professionals.